Adding moments to history of Anesthesia of Nepal: Truth or fiction? - Sharma, Apurb (Journal of Society of Anesthesiologists of Nepal, 2019)
This article describes about a person who might have served as anesthesia provider during 1930s at the Bir Hospital, Kathmandu, Nepal. However, concrete evidence of the person’s work as an anesthesia provider has not been found yet.